230k views
4 votes
Idk what the right answer is

Idk what the right answer is-example-1
User Ak
by
5.1k points

1 Answer

4 votes

Answer:

f(x) = x^3 - 2(x)^2+3(x)-1

Explanation:

Since h(x) is the combination of function f and g, you have to seprate g(x) from f(x).

To do this, you subsitute x for each and every (8-4x) because g(x)=(8-4x)

h(x) = (8-4x)^3 - 2(8-4x)^2+3(8-4x)-1 so

f(x) = x^3 - 2(x)^2+3(x)-1

User Scosman
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.